Chikungunya Fever Cases Identified in the Veterans Health Administration System, 2014. - Tara Perti; Cynthia A Lucero-Obusan; Patricia L Schirmer; Mark A Winters; Mark Holodniy (Public Library of Science (PLoS), 2016)
BACKGROUND:During December 2013, the first locally transmitted chikungunya virus (CHIKV) infections in the Americas were reported in the Caribbean. Although CHIKV infection is rarely fatal, risk for severe disease increases with age and medical comorbidities. Herein we describe characteristics of Veterans Health Administration (VHA) patients with CHIKV infection and, among those with infections diagnosed in Puerto Rico, investigated risk factors for hospitalization. METHODOLOGY:We queried VHA's national electronic medical records to identify patients with CHIKV testing during 2014. Demographics, clinical history, laboratory results, and outcomes were abstracted. We investigated risk factors for hospitalization among patients with laboratory-confirmed CHIKV infection in Puerto Rico. PRINCIPAL FINDINGS:We identified 180 laboratory-confirmed CHIKV infections; 148 (82.2%) were diagnosed in Puerto Rico, and 32 (17.8%) were diagnosed among returning travelers elsewhere in the United States. In Puerto Rico, where more patients were hospitalized (55.4% versus 20.0%) and died (4.1% versus 0%), risk for hospitalization increased with age (relative risk [RR]/each 10-year increase, 1.19; 95% confidence interval [CI], 1.06-1.32) and, adjusted for age, increased among patients with congestive heart failure (RR, 1.58; 95% CI, 1.25-1.99), chronic kidney disease (RR, 1.52; 95% CI, 1.19-1.94), diabetes mellitus (RR, 1.39; 95% CI, 1.06-1.84), or chronic lung disease (RR, 1.37; 95% CI, 1.03-1.82). CONCLUSIONS/SIGNIFICANCE:CHIKV infection is an emerging problem among Veterans residing in or visiting areas with CHIKV transmission. Although overall mortality rates are low, clinicians in affected areas should be aware that older patients and patients with comorbidities may be at increased risk for severe disease.